2020
DOI: 10.1021/acs.biochem.0c00490
|View full text |Cite
|
Sign up to set email alerts
|

Cautionary Tale of Using Tris(alkyl)phosphine Reducing Agents with NAD+-Dependent Enzymes

Abstract: Protein biochemistry protocols typically include disulfide bond reducing agents to guard against unwanted thiol oxidation and protein aggregation. Commonly used disulfide bond reducing agents include dithiothreitol, β-mercaptoethanol, glutathione, and the tris(alkyl)phosphine compounds tris(2-carboxyethyl)phosphine (TCEP) and tris(3-hydroxypropyl)phosphine (THPP). While studying the catalytic activity of the NAD(P)H-dependent enzyme Δ 1 -pyrroline-5-carboxylate reductase, we unexpectedly observed a rapid non-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Tris­(hydroxymethyl)­phosphine, P­(CH 2 OH) 3 , is a well-known and easily prepared C 3 -symmetric phosphino-triol, which is routinely employed in industry and academia, not only for the preparation of water-soluble metal complexes but also as a flame retardant, a multipurpose reductant, and a medicinal O 2 -scavanger . The chemistry of the higher homologues P­[(CH 2 ) n OH] 3 ( n = 2, 3) has been explored as well, albeit only tris­(hydroxypropyl)­phosphine ( n = 3) is regularly used as a mild reductant for the reductive cleavage of disulfide bonds . In comparison to these alkyl phosphino-triols, our knowledge on related hydroxylated aryl phosphines is still limited; i.e., only a few reports on the two most simple Ph 3 P-based phosphino-triols, namely, P­(C 6 H 4 - o -OH) 3 and P­(C 6 H 4 - o -CH 2 OH) 3 (and their derivatives), have been published to date (see Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Tris­(hydroxymethyl)­phosphine, P­(CH 2 OH) 3 , is a well-known and easily prepared C 3 -symmetric phosphino-triol, which is routinely employed in industry and academia, not only for the preparation of water-soluble metal complexes but also as a flame retardant, a multipurpose reductant, and a medicinal O 2 -scavanger . The chemistry of the higher homologues P­[(CH 2 ) n OH] 3 ( n = 2, 3) has been explored as well, albeit only tris­(hydroxypropyl)­phosphine ( n = 3) is regularly used as a mild reductant for the reductive cleavage of disulfide bonds . In comparison to these alkyl phosphino-triols, our knowledge on related hydroxylated aryl phosphines is still limited; i.e., only a few reports on the two most simple Ph 3 P-based phosphino-triols, namely, P­(C 6 H 4 - o -OH) 3 and P­(C 6 H 4 - o -CH 2 OH) 3 (and their derivatives), have been published to date (see Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Support for a puckered ring during the transition from oxidized to reduced cofactor has been described in a structure of horse liver alcohol dehydrogenase, where the puckered nicotinamide ring was in a quasi-boat conformation with bond angles and distances suggesting a strained molecule that could mimic a transition state (Plapp & Ramaswamy, 2012). Interestingly, NAD(P)-adducts with reducing agents have been reported previously, including with TCEP (Patel et al, 2020) and also with DTT (Paidimuddala et al, 2018), and were often found to have a more puckered nicotinamide ring. S2), suggestive of a transition-state-like conformation.…”
Section: Idh1 R132q Maintains a Typical Closed Conformation In Its Ic...mentioning
confidence: 65%
“…Reduction of NAD + to yield NADH generates the well-known absorbance at 340 nm and an analogous absorbance occurs after hydride addition to NaAD (Figure S3A,B). It is also established that thiols and a variety of nucleophiles including tris­(alkyl)­phosphine reductants can reversibly add to C4 of the pyridinium ring of nicotinamides to generate similar absorbances. Thus, we reasoned that a Cys221-pyridine adduct (intermediates 1 and 2, Figure ) would also be observed by UV–vis spectroscopy if formed at sufficient abundance. Indeed, we demonstrated that an absorbance with a maximum near 370 nm is generated when NAD + was titrated into the WT or S127A forms of LarB, with all solutions argon purged to prevent carboxylation (Figure S3C,D).…”
Section: Resultsmentioning
confidence: 97%